APPLICATION OF THE DIJKSTRA ALGORITHM IN THE DISSEMINATION OF LOCATION OF CERTIFIED TEACHING STAF OF LAMPUNG PROVINCE PUBLIC ELEMENTARY SCHOOLS - Arfida, Septilia; -, Amnah; Wibowo, Hariyanto (Prosiding International conference on Information Technology and Business (ICITB), 2018)
Provision and provision of information currently takes place very quickly in human life. The necessary information must be easily accessed by various parties who have interests to be more effective and efficient. One of them is information in the world of education, occupying a very important role because education and information is a vehicle in actualizing all the available potential so that it can improve and develop human resources. One of the information needed is knowing the location of certified public elementary school educators in Lampung Province. This mapping application is a distribution from the location of certified educators by applying the Dijkstra Algorithm. So that with this application, it is expected that the data collection of professional teachers or those who have been certified for the State Elementary School level with the Dijkstra Algorithm in Lampung Province can be monitored and known by the Education Office of Bandar Lampung city. Besides that it also provides information to other parties who need it.Keywords:Mapping, Location of Educators, Dijkstra Algorithm;